Heat Stress Promotes Nitrogen Accumulation in Meristems via Apical Blade Erosion in a Brown Macroalga With Intercalary Growth - Endo, Hikaru; Inomata, Eri; Gao, Xu; Kinoshita, Junji; Sato, Yoichi; Agatsuma, Yukio (Frontiers in Marine Science, 2020)
Heat stress is known to induce photoinhibition, leaf senescence, and nutrient remobilization in terrestrial plants with apical growth; however, its effect on blade erosion and associated-changes in chemical compositions has rarely been studied in marine macroalgae with intercalary growth such as kelp. The present study examined the combined effects of ocean warming (23 and 26 °C), irradiance (30 and 180 µmol m-2 s-1), and nutrient enrichment (enriched and non-enriched) on photosystem II maximum efficiency (Fv/Fm) in the kelp Eisenia bicyclis. It also investigated the effect of ocean warming on the kelp’s relative growth rates based on five morphological parameters and three chemical compositions (carbon, nitrogen, and phlorotannnins). A warming effect on photoinhibition (i.e., decline in Fv/Fm) was only detected under the higher irradiance combined with nutrient-enrichment condition. Under this condition, elevated temperature decreased relative growth rates to negative values, indicating occurrence of apical blade erosion. Temperature elevation also caused increases in nitrogen and phlorotannin contents within the whole body, but not carbon content. Moreover, nitrogen content in the meristems at 26ºC was higher than that at 23ºC, although such a difference was not observed with phlorotannin content. These results suggested that heat-induced apical blade erosion promoted nitrogen accumulation in the meristems, located in the lower part of the blade, in E. bicyclis.